English Language Teaching (ELT) for Special Needs Learners: Strategies for Speech Impairments Students - Nur Fitria, Tira (Teaching English as Foreign Language, Literature and Linguisticss, 2025)
This research describes English Language Teaching (ELT) for special needs learners for example speech impairment students. This study employs a library research method. The analysis shows that teaching English to students with speech impairments requires adaptive strategies to develop communication skills through non-verbal and assistive methods. Since verbal communication is challenging, alternative approaches like sign language, writing, and technology-based aids are essential. A multisensory approach involving sight, touch, hearing, and movement enhances comprehension, while multimodal techniques using images, videos, and symbols help clarify word meanings. Assistive tools such as augmentative communication devices and speech-to-text software support students' learning processes. To reduce anxiety and enhance participation, teachers should provide extra time, allow repetitive practice, and create an inclusive environment. Challenges include pronunciation difficulties, limited verbal expression, and low confidence in speaking activities, often leading to reduced engagement. Traditional assessments may not accurately measure students’ abilities, necessitating alternative evaluation methods. Additionally, many teachers lack training in specialized teaching techniques, highlighting the need for professional development and classroom adaptations. By integrating supportive teaching strategies, collaborative learning, and game-based activities, English learning for speech-impaired students can be more effective, engaging, and inclusive.